Teachers' Experience in Implementing the Independent Curriculum in Junior High Schools - Sinta, Sinta (INDONESIAN JOURNAL OF SUSTAINABILITY, 2025)
Teachers nowadays face their own challenges in conducting teaching activities in their classrooms based on the Merdeka Curriculum. Investigating teachers' experiences in implementing the Merdeka Curriculum in Junior High Schools (SMP), focusing on the challenges faced and the benefits obtained. A qualitative research method was employed, with data obtained through the analysis of internal school documents and teacher reflections. The findings indicate that teachers encounter various challenges in adopting the Merdeka Curriculum, particularly in understanding its concepts. However, they also find benefits from the flexibility provided by the curriculum, enabling them to design more relevant and engaging learning experiences for students. Teachers also undergo a change in their roles, shifting from traditional instructors to facilitators of learning more oriented towards developing students' skills. These findings underscore the importance of appropriate support and training for teachers in implementing the Merdeka Curriculum. The implications of this research emphasize the need for better supportive.Keywords : Teacher, Independent Curriculum, Strategy